The versatile roles of ADAM8 in cancer cell migration, mechanics, and extracellular matrix remodeling - Mierke, Claudia Tanja (Frontiers in Cell and Developmental Biology, 2023)
The posttranslational proteolytic cleavage is a unique and irreversible process that governs the function and half-life of numerous proteins. Thereby the role of the family of A disintegrin and metalloproteases (ADAMs) plays a leading part. A member of this family, ADAM8, has gained attention in regulating disorders, such as neurogenerative diseases, immune function and cancer, by attenuating the function of proteins nearby the extracellular membrane leaflet. This process of “ectodomain shedding” can alter the turnover rate of a number of transmembrane proteins that function in cell adhesion and receptor signal transduction. In the past, the major focus of research about ADAMs have been on neurogenerative diseases, such as Alzheimer, however, there seems to evidence for a connection between ADAM8 and cancer. The role of ADAMs in the field of cancer research has gained recent attention, but it has been not yet been extensively addressed. Thus, this review article highlights the various roles of ADAM8 with particular emphasis on pathological conditions, such as cancer and malignant cancer progression. Here, the shedding function, direct and indirect matrix degradation, effects on cancer cell mobility and transmigration, and the interplay of ADAM8 with matrix-embedded neighboring cells are presented and discussed. Moreover, the most probable mechanical impact of ADAM8 on cancer cells and their matrix environment is addressed and debated. In summary, this review presents recent advances in substrates/ligands and functions of ADAM8 in its new role in cancer and its potential link to cell mechanical properties and discusses matrix mechanics modifying properties. A deeper comprehension of the regulatory mechanisms governing the expression, subcellular localization, and activity of ADAM8 is expected to reveal appropriate drug targets that will permit a more tailored and fine-tuned modification of its proteolytic activity in cancer development and metastasis.